Melatonin Attenuates Endothelial-to-Mesenchymal Transition of Glomerular Endothelial Cells via Regulating miR-497/ROCK in Diabetic Nephropathy - Feng Liu; Siqi Zhang; Ruisi Xu; Shuohui Gao; Jian Yin (Karger Publishers, 2018)
Background/Aims: Endothelial-to-mesenchymal transition (EndMT) of glomerular endothelial cells (GEnCs) can induce albuminuria in diabetic nephropathy. Melatonin attenuates diabetic nephropathy, but its role and mechanism in EndMT of GEnCs in diabetic nephropathy remain unknown. Methods: The effect of melatonin on EndMT induced by transforming growth factor (TGF)-β2 in human renal GEnCs was determined by assaying the expression of endothelial marker cells (VE-cadherin and CD31) and mesenchymal cells (α-SMA and Snail), as well as monolayer permeability. The molecular mechanism of melatonin in these processes was focused on miR-497/ROCK signaling. Furthermore, the effect and mechanism of melatonin in EndMT were confirmed in glomeruli of rats with streptozotocin-induced diabetes. Results: Melatonin increased expression of VE-cadherin and CD31 and inhibited α-SMA and Snail levels that were altered by TGF-β2 in GEnCs. Melatonin treatment reduced expression and activity of ROCK1 and ROCK2, which suppressed TGF-β2-induced hyperpermeability of GEnCs and EndMT of GEnCs. Melatonin reduced ROCK1 and ROCK2 expression and activity in TGF-β2-stimulated GEnCs by enhancing expression of miR-497, which targets ROCK1 and ROCK2. Furthermore, we found that melatonin inhibited EndMT in glomeruli and albuminuria in rats with streptozotocin-induced diabetes. MiR-497 expression increased, whereas ROCK1 and ROCK2 expression and activity decreased in melatonin-treated diabetic rats. Conclusion: Melatonin attenuated EndMT of GEnCs via regulating miR-497/ROCK signaling in diabetic nephropathy. This study improves understanding of EndMT and the role of melatonin in diabetic nephropathy.